RANCANG BANGUN DAN PENGUJIAN MESIN PENGADUK SUSU KEDELAI DENGAN VARIASI BENTUK PENGADUK - Irawan, Candra; Suwandi, Dedi; Kusmayadi, Adi; Rohmat, Yusup Nur (Politeknik Negeri Sriwijaya, Indonesia, 2024)
Haurgeulis District in Indramayu Regency is known as one of the areas producing quality soybeans. In this region, many mothers who are members of UMKM take advantage of this potential by producing soy milk. However, the process of making soy milk is still manual, one of which is the stirring stage during heating. This often results in inconsistent results and requires quite a lot of effort. To overcome this problem, research was carried out to design and build a soy milk mixing machine expected to increase production efficiency and quality, as well as support UMKM in developing their businesses. The purpose of this design is to make the mixing process easier, the method used is how much power is needed, how much production capacity, how much electricity is used, and which form of the stirrer can produce fast, consistent, and even mixing. The result of this design is a motor power of around 0.18 kW. Apart from that, stirrer C required the shortest time with an average of 2.54 seconds. The process of cooking milk in one production of 4 liters takes 1 hour and 6 minutes over low heat. At 100 rpm rotation, the power consumed is 844.2 W. The electricity costs to operate this machine are around IDR 7,000-IDR 10,000 per month to produce 1 hour per day.